ANALISIS KAPABILITAS DINAMIS IVORY RADIO DALAM MENGHADAPI ERA KONVERGENSI DIGITAL - Asrunputri, Aisyah Pia; Zulkarnaen, Mutiara (JURISMA : Jurnal Riset Bisnis & Manajemen, 2020)
As the technology continues to evolve, it creates opportunities and threats for all the organizations involved in the industry. Dynamic capability is needed to respond those changes for the organizations to survive. Dynamic capability is organizations’ ability to integrate, build, and reconfigure its internal and external competency in responding continuous change, which is a good opportunity for the organization to evolve and grow. With dynamic capability, it can help organizations in reaching its competitive position be it for short term or long term. However, in order to build dynamic capability, organizations must have capacity to shape and sense opportunities and threats also to seize those opportunities also to reconfigure organizational resources be it tangible or intangible resources. Ivory Radio is one of the organizations that succeed to create an infrastructure and mechanism in facing the era of digital convergence. The readiness of Ivory Radio comes from its dynamic capability that makes Ivory Radio stands still in maintaining its competitive position in the industry. Key words: Dynamic Capability, Ivory Radio, Era of Digital Convergence